Magnetic Deep Eutectic Solvents Based Adsorbents For The Removal Of Selected Non-Streoidal Antiinflammotary Drugs - Husin, Nor Aniisah (2020)
In this study, material based on magnetic choline chloride-butyl imidazole (Fe3O4@ChCl-BuIM) was synthesise via simple co-precipitation method for removal of diclofenac and naproxen from water sample. The synthesised material was characterized by using analytical instrument such as Fourier transform infrared spectroscopy (FTIR), CHN elemental analyser, vibrating sample magnetometer (VSM), scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffractometer (XRD), thermogravimetric analyser (TGA), and Brunauer-Emmet-Teller (BET) surface analyser. Preliminary adsorption study of Fe3O4@ChCl-BuIM has showed excellent adsorption capacity for removal of diclofenac and naproxen from water samples compared to unmodified Fe3O4. Both targeted analytes were attracted to the Fe3O4@ChCl-BuIM particles by U  U interaction and hydrogen bonding, thus improved the adsorption capacity.